Pengaruh Sistem Perpajakan, Tarif Pajak, Keadilan Pajak dan Pemeriksaan Pajak terhadap Etika Penggelapan Pajak - Cindi Faujia Putri; Mumun Maemunah; Carolyn Lukita (Syntax Literate, 2023)
This research was conducted with the aim of analyzing the influence of the tax system, tax rates, tax fairness and tax audits on the ethics of tax evasion. Data collection is used using questionnaires. The sample in this study were taxpayers registered at KPP Pratama Karawang with a sample size of 100 taxpayer respondents. The data analysis used is a hypothesis testing method using Structural Equation Modeling (SEM) with the help of SmartPLS version 3.0 software. The research results show that the tax system and tax rates have no effect on the ethics of tax evasion, while tax justice and tax audits have an effect on the ethics of tax evasion.